Effects of Covid-19 pandemic on nutritional habits, lifestyle changes and dental trauma frequency of children with autism: a cross-sectional study - Hulya Cerci Akcay; Duygu Safci; Yelda Kasimoglu; Gamze Aren; Recep Guloğlu; Murat Coskun; Yaşar Tanir; Meryem Merve Oren; Arzu Pinar Erdem (BMC Oral Health)
Abstract Background The Covid-19 pandemic has disrupted daily routines and lifestyle habits, affecting the psychological well-being and dietary habits of individuals, especially children with autism spectrum disorder (ASD). This study aims to evaluate the susceptibility of children with ASD to changes in nutritional habits, lifestyle, and dental trauma during the pandemic related with oral health and compare them with healthy children. Methods This study, conducted at Istanbul University, involves children aged 3–14 diagnosed with ASD at the Department of Child and Adolescent Psychiatry, and healthy children who visited the Department of Pedodontics. Parents provide written informed consent, and a questionnaire covering various aspects of their child’s health and habits is used. Intraoral examinations are conducted for both groups, recording any trauma history or signs, and evaluating possible causes and risk factors. All data were obtained and analysed by SPSS software program version 23.0 with descriptive statistics calculation, Chi square test, Kolmogorov Smirnov, the Mann-Whitney U test, t test and McNemar test was used with p value fixed at 0.05. Results The results show significant differences between children with ASD and the control group in terms of dental health. Children with ASD had lower dmft and DMFT indices, indicating better dental health (p = 0.005). However, the frequency of dental trauma was similar between the groups (p = 0.685). Additionally, the control group exhibited more significant changes in dietary habits during the pandemic, with a higher tendency for snacking throughout the day (p = 0.027). During lockdowns, parents of children with ASD were statistically more likely to provide junk food when their child was irritable (p < 0.001). Changes in physical activity levels also differed, with a more pronounced decrease in the control group (p < 0.001). Furthermore, children with ASD experienced a statistically significant higher rate of disruption in daily routines and inability to participate in social activities and courses (p < 0,001). Conclusion This study sheds light on the unique challenges faced by children with ASD, particularly in terms of dental health and related behaviors. It underscores the importance of interventions to ensure optimal oral health outcomes for this population, especially during periods of disruption like the Covid-19 pandemic.